2016
DOI: 10.1038/srep21121
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hydrogen peroxide increases biofilm formation by inducing exopolysaccharide production in Acinetobacter oleivorans DR1

Abstract: In this study, we investigated differentially expressed proteins in Acinetobacter oleivorans cells during planktonic and biofilm growth by using 2-dimensional gel electrophoresis combined with matrixassisted laser desorption time-of-flight mass spectrometry. We focused on the role of oxidative stress resistance during biofilm formation using mutants defective in alkyl hydroperoxide reductase (AhpC) because its production in aged biofilms was enhanced compared to that in planktonic cells. Results obtained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 49 publications
(66 reference statements)
2
42
0
4
Order By: Relevance
“…Biosynthesis of purines and pyrimidines depends on the availability of histidine and DNA synthesis is linked to e-DNA release, which is also required for the biofilm formation 43 . In addition, HutU has been reported to have biofilm formation of Acinetobacter oleivorans 44 and Acinetobacter baumannii 43 . It is likely that down-regulation of HutU by vanillic acid could also be responsible for the reduction of biofilm formation in S. marcescens .…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of purines and pyrimidines depends on the availability of histidine and DNA synthesis is linked to e-DNA release, which is also required for the biofilm formation 43 . In addition, HutU has been reported to have biofilm formation of Acinetobacter oleivorans 44 and Acinetobacter baumannii 43 . It is likely that down-regulation of HutU by vanillic acid could also be responsible for the reduction of biofilm formation in S. marcescens .…”
Section: Resultsmentioning
confidence: 99%
“…The polysaccharide overproduction in the EPS matrix after NAC exposure could be related to the oxidative imbalance in the treated biofilm. It has been demonstrated that EPS polysaccharides played a critical role in relief of the oxygen stress in several microorganisms such as Pseudomonas putida, Sinorhizobium meliloti and Acinetobacter oleivorans [59,[64][65][66]. Indeed, some polysaccharides can scavenge hydroxyl radicals, inhibiting lipid and protein oxidation [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some polysaccharides can scavenge hydroxyl radicals, inhibiting lipid and protein oxidation [67,68]. Interestingly, the role of the redox-sensing transcription factor OxyR in the regulation of EPS exopolysaccharide production has been reported [65,69]. Burbank and Roper [69] demonstrated that ∆oxyR mutants negatively regulated the gene expression of exopolysaccharides, making the mutants more prone to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…S4A). The genome of A. oleivorans DR1 contains exopolysaccharide (EPS) operons: poly-N-acetyl glucosamine operons and the K locus (39). The expression of genes involved in the EPS complex was increased by Ͼ3.0-fold in the sinE mutant (supplemental Fig.…”
Section: Sine Functioning As a Ribonuclease And Inhibiting Protein Symentioning
confidence: 99%